Characterize the firewood and charcoal production and consumption patterns in the Northern part of Ethiopia - Binega Derebe; Asmamaw Alemu; Zebene Asfaw (Sustainable Futures, 2025)
Wood-based fuels remain a primary source of energy for many households in Ethiopia, particularly in rural and urban communities with limited access to alternative energy sources like biogas and electricity. Although electricity is available, particularly in urban areas, it is unreliable as it frequently experiences outages. Therefore, this study characterizes the production and consumption patterns of firewood and charcoal in the Northern part of Ethiopia, focusing on rural and urban disparities. Using a mixed-methods approach, data were collected from 276 households to analyze fuel usage, sourcing, management practices, and preferred tree species. Results reveal significant differences in fuel production and consumption between rural and urban areas, with rural households predominantly engaged in charcoal production and firewood collection, while urban households rely heavily on market purchases. On average, rural households produced 62.52 bundles of firewood and 172.98 sacks of charcoal annually, while urban households produced 43.14 bundles of firewood and did not produce charcoal. Firewood and charcoal are essential for cooking, heating, and other domestic uses, with Olea europaea, Anogeissus leiocarpa, Eucalyptus globulus, Acacia polyacantha and Acacia abyssinica being the most preferred species due to their high calorific value and availability. The study highlights the reliance on natural forests and the need for sustainable management practices to mitigate deforestation and ensure long-term energy security. Policy recommendations include promoting agroforestry, sustainable harvesting, and alternative energy sources to reduce pressure on forest resources.